Cytotoxic KLRG1+ IL-7R- effector CD8+ T cells distinguish kidney transplant recipients controlling cytomegalovirus reactivation - Sun, Yumeng; Sen, Subha; Parmar, Rajesh; Arakawa-Hoyt, Janice; Cappelletti, Monica; Rossetti, Maura; Gjertson, David W.; Sigdel, Tara K.; Sarwal, Minnie M.; Schaenman, Joanna M.; Bunnapradist, Suphamai; Lanier, Lewis L.; et al. (Frontiers in Immunology, 2025)
IntroductionCytomegalovirus (CMV) viremia remains a major contributor to clinical complications in solid organ transplant (SOT) patients, including organ injury, morbidity and mortality. Given their critical role in antiviral defense, CD8+ T cells are essential for protective immunity against CMV.MethodsUsing single-cell RNA sequencing, we investigated the transcriptional signatures and developmental lineages of CD8+ T cells in eight immunosuppressed kidney transplant recipients (KTRs) who received organs from CMV-seropositive donors. Results were validated in a cohort of 62 KTRs using immunophenotyping.ResultsOur data revealed a significant influence of CMV serostatus on transcriptional variance of CD8+ memory T cells, associating with the first principal component from a global analysis of CD8+ T cells (p =0.0406), forming a continuum with five principal differentiation trajectories driven by CMV primary infection or reactivation. Following CMV primary infection, CD8+ T cells were hallmarked by restrained effector-memory differentiation. CD8+ T cells during CMV reactivation diverged non-linearly into senescent-like cells with signatures of arrested cell cycle, diminished translational activity and downregulated ZNF683 and longitudinally expanding effector cells with robust cytotoxic potential and upregulated ZNF683, acting as a reservoir for long-lived effector cells supporting long-term protection. Notably, CD28lo KLRG1hi IL-7R (CD127)lo HLA-DRhi CD8+ T cells present prior to the detection of viremia in CMV-seropositive patients emerged as a key feature distinguishing patients who did or did not undergo CMV reactivation after prophylaxis discontinuation (p =0.0163). Frequencies of these cells were also positively correlated with CMV-stimulated secretion of IFN-γ (p =0.0494), TNF-α (p =0.0358), MIP-1α (p =0.0262), MIP-1β (p =0.0043).DiscussionThese results provide insights into the transcriptional regulation that influences the generation of CD8+ T cell immunity to CMV and may inform strategics for monitoring host immune response to CMV to better identify and introduce therapeutic intervention to patients at risk of developing clinically significant CMV viremia.